Development of Environmental Pollution Electronic Module in Kudus Regency on Project-Based Learning (PjBL) for Junior High School Students - Ulfa, Dwi Mariana; Ngabekti, Sri (Journal of Environmental and Science Education, 2022)
This study aims to analyze the characteristics, feasibility, and readability of the PjBL-Based Environmental Pollution E-module for Junior High School Students. The type of research conducted is Research and Development (R&D). The steps of this research include potentials and problems, data collection, product design, design validation, design revision, and small-scale product trials. The research instrument was in the form of a media expert questionnaire, material, and readability experts. The results show that the developed E-module has characteristics, namely the developed E-module with PjBL syntax, equipped with video. The developed e-module is suitable for use as a learning medium with an average percentage of media validation and material validation obtaining an average of 92.06%, each of which is in the very good category. The PjBL-Based PjBL-Based Environmental Pollution E-module for Junior High School Students uses language that is easily understood by students so that students can understand the material. Based on the research, it can be concluded that the PjBL-Based Environmental Pollution E-module for Junior High School students has PjBL syntax and is equipped with a very decent supporting video and obtains very good criteria in the readability test and feasibility test in science learning.